COMPARATIVE ANALYSIS OF THE NONPOLAR FRACTION OF THE AERIAL AND UNDERGROUND PARTS OF THE LIMONIUM GMELINII PLANTS BY THE GC-MS METHOD - A.I. Zhussupova; Y.S. Ikhsanov; A.A. Mamutova; G.E. Zhusupova (Academic Scientific Journal of Chemistry, 2019)
This article discusses the chemical composition of the non-polar fraction obtained from the aerial and underground parts of Limonium gmelinii (Willd.) harvested in the Almaty region in 2018. Extracts were obtained by the method of solvent extraction with hexane and studied by means of chromato-mass spectrometry on a gas chromatograph with a mass-selective detector. As a result, 22 compounds were isolated from the aerial part of Limonium gmelinii plant, out of which dominating both quantitatively and qualitatively are hydrocarbons, such as genicosane and eicosane and tricosane; quinoline and phytol derivatives were isolated as well. High content of phytol acetate related to derivatives of acyclic diterpene alcohols has been revealed. In addition, the higher alcohol 3,7,11,15-tetramethyl-2-hexadecan-1-ol has been identified. Analysis of the non-polar extract obtained from the roots of Limonium gmelinii allowed us to isolate 14 compounds, out of which the major share in the amount belongs to the esters of higher carboxylic acids and hydrocarbons. Esters are represented as ethyl esters of hexadecanoic, oleic and linoleic acids with prevalence of polyene acids in them. Among the hydrocarbons, tridecane, tetradecane, heptadecane, octadecane and tetracosane are the most abundant.